Tinjauan Pustaka terhadap Tatalaksana Terkini Ulkus Kornea Jamur Akibat Salah Penggunaan Lensa Kontak - Satrio Arief Setiawan; Muhamad; Santi Anugrahsari Anugrahsari (Jurnal MedScientiae, 2023)
Microbial keratitis can cause corneal ulcers that can threaten vision. Keratitis is the leading cause of global corneal blindness with an estimated incidence of 2.5-799 cases per 100,000 population/year. Corneal ulcers contribute 5% of blindness worldwide and are the most common cause of corneal blindness in the developing countries. This is a review over articles from electronic databases which focuses on the topic relevance, research methods, subjects, and the results. The data were collected from NCBI, AAOJournalt and Google Scholar with keywords “Fungal”, “Corneal Ulcer”, “Treatment”, “Contact Lens”, “Jamur”, “Ulkus Kornea”, “Terapi”, and “Lensa Kontak”. The inclusion criteria are published from January 2012 to July 2022, a study of humans, available in full text, written English or Indonesian. Natamycin 5% is effective in the treatment of fungal keratitis, voriconazole is more effective against fungal keratitis, and oral posaconazole can serve as an effective treatment for refractory Paecilomyces keratitis, which is resistant to conventional therapy. If the use of drugs that are not enough to treat fungal keratitis, requires action intervention. In treatment with action there is novelty in the action of the combination of CLX and acellular porcine corneal stroma (APCS). Keywords: literature review, management, microbial keratitis